(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
This article has no abstract. The first 100 words appear below: A 50-year-old female got admitted on June 18, 2019 with complaints of central chest pain for three years and dizziness for the last two months. The chest pain was compressive in nature, moderate to severe in intensity and radiating to the medial side of the left upper limb and neck. It used to get aggravated during exertion and initially relieved by taking rest but later she had to take medicine to relieve the chest pain. The pain was not associated with meal, palpitation, dyspnoea, cough or fever. She also complained of dizziness and easy fatigability while walking for the last two months.